Cytotoxicity of Compounds Isolated from Usnea aciculifera - Shyaula, Sajan L; Shah, Teresa; Rathnayaka, Rajitha Kalum; Samarakoon, Sameera R; Manandhar, Erendra; Yue, Jian Min; Manandhar, Mangala Devi (Journal of Nepal Chemical Society, 2023)
Atranorin 1, Usnic acid 2, and D-Arabinitol 3 were isolated from Usnea aciculifera by extensive column chromatography. The structures were elucidated based on the comprehensive spectral analysis including FT IR, GC MS, ESI MS, 13C NMR, and 1H NMR. The compounds were evaluated for their cytotoxic activity against LN-229 glioblastoma cancer cell line by performing Sulforhodamine B assay (SRB). Usnic acid 2 showed strong cytotoxic activity against LN-229 glioblastoma cancer cell with an IC50 value of 3.09 μg/mL.